Avaliação da Rede de Referência como estratégia de transferência de tecnologia na perspectiva dos agricultores - Perera, Apes Roberto Falcão (2009)
The production of technological knowledge in Brazil was intensified during a historical moment in which the interests of the instituted powers weren t corresponding to the necessities of the productive sector. The role of the official organs of rural extension and research was to introduce Brazil into the international context of agricultural modernization. This would attend the interests of the agricultural inputs production industry and of the food processing industry. As the interests became more distant there was stockage of non-used technologies with consequent effort of these organizations for the adoption of these technologies. Intending to avoid the stock rise, some initiatives have been implemented. These initiatives use especially participative methodologies associated with social organization strategies that promote an approach between researchers and farmers. They also seek for a better definition of the research problems, making it easier to use the produced knowledge. The aim of this work was to analyze the Reference Network methodology as a tool for this approach. Based on result evaluation and on the insight of the farmers involved in works which used this methodology we suggest that there should be more caution to form these networks as well as associate them to other strategies for the reduction of technology stocks